PEMBUATAN TEH DAUN GAMBIR (Uncaria Gambir Roxb) ASAL KALIMANTAN BARAT PADA VARIASI SUHU PENGERINGAN - Iskandar, Dodi; Ramdhan, Noval Aditya (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2020)
Gambir (Uncaria gambir roxb) belongs to family Rubiaceae and genus Uncaria. The content of chemical compounds in plants is called phytochemicals. Plants can be a source of chemical compounds that can be used as medicine. The method used in this study is an experiment in the Laboratory, using qualitative phytochemical testing following procedures (Tariq and Reyaz, 2012) and total phenol testing using the Folin-Ciocalteau method from Xu and Chang (2007). Gambir leaf tea characteristics approaching SNI 2013 are at a temperature of 90oC with a moisture content of 14, 3223% (db), 16.8312%. Ash content of 90oC 3,9326 with total phenol levels contained in gambier leaves 3.9 mg GAE/10mg. The compounds contained in gambir leaves include flavonoids, tannins and saponins.